1997
DOI: 10.1103/physrevb.56.15725
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity of In chains on Si(111)

Abstract: The electronic structure of the Si͑111͒-In͑4ϫ1͒ system, between the Fermi level and the vacuum level, has been studied using inverse photoemission. Single domain 4ϫ1 overlayers were grown on vicinal Si͑111͒ surfaces that were offcut by 3°towards ͓ 1 12͔. In contrast to an earlier inverse photoemission study of this system, which was performed on a multidomain sample, but in agreement with recent photoemission and STM studies, the overlayer system was found to be metallic. A clear Fermi level crossing was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 16 publications
7
57
1
Order By: Relevance
“…It was suggested in the earlier electronic studies that the system was metallic with a high degree of asymmetry [10,11], and that furthermore there existed a half-filled band [11]. Our measurements are precise enough to determine the exact band filling, as well as the degree of coupling between the chains from the bandstructure.…”
Section: X1 Reconstruction: 1deg [4]supporting
confidence: 50%
See 1 more Smart Citation
“…It was suggested in the earlier electronic studies that the system was metallic with a high degree of asymmetry [10,11], and that furthermore there existed a half-filled band [11]. Our measurements are precise enough to determine the exact band filling, as well as the degree of coupling between the chains from the bandstructure.…”
Section: X1 Reconstruction: 1deg [4]supporting
confidence: 50%
“…This system was characterized structurally [5][6][7][8][9] and electronically [10,11]. In these works it was found that the In atoms were organized into linear chains of atoms, and that the electronic properties appeared to be highly anisotropic, with metallic behavior indicated by band crossings of E F along the chains.…”
Section: X1 Reconstruction: 1deg [4]mentioning
confidence: 99%
“…It has been found that at approximately 0.5 monolayer (ML), the 4 Â 1 phase of In on Si(111) is quasione-dimensional, with the In chains aligned along the step edges [9]. Angle-resolved photoemission (ARPES) and inverse photoemission (IPES) studies of the system [10,11] have identified a`metallic' state aligned with the step edges.…”
Section: Introductionmentioning
confidence: 98%
“…As one can imagine from this atomic arrangement, its surface electronic state is highly anisotropic. From photoemission spectroscopies [42,43], it is metallic along the In chains, while insulating in the perpendicular direction. In other words, the electrons are mobile along the In chains, while they can hop only with considerable energy to neighbouring chains.…”
Section: The Si(1 1 1) 7 â 7 Surface: a Poor Metal Or Mott Insulator?mentioning
confidence: 99%